Nutrient release dynamics from decomposing organic materials and their mulching-effect on pearl millet yields in a low-input Sahelian cropping system - Ibrahim Ali; Abaidoo R. C; Tawaye Iliasso Aboubacar Dan Kassoua; Tawaye Iliasso Aboubacar Dan Kassoua; Fatondji Dougbedji (Springer, 2023)
This article is Published by Springer, 2017 and is also available at 10.1007/s10705-018-9928-4